NEGOTIATING ENGLISH USE IN COASTAL TOURISM : DECOLONIZING ELT AND COMMUNICATIVE FUNCTIONALITY - Faiqoh Tsuroya; Ahmad Munir; Muhaimin Abdullah (English Study Program University of Pasir Pengaraian, 2026)
This study investigates the tension between institutional English norms and students’ lived communicative practices in a coastal tourism context, addressing a gap in decolonizing ELT research that has largely focused on classroom-based discourse rather than real-life interaction. Using an exploratory qualitative design, the study involved one English teacher and nine senior high school students in Situbondo, East Java, Indonesia, who regularly interacted with international tourists in local tourism settings. Data were collected through semi-structured interviews, observations, and documentation, and analyzed thematically. The findings reveal a mismatch between classroom-oriented English instruction, which prioritizes grammatical correctness and native-speaker norms, and tourism-based communication, which relies on intelligibility, code-mixing, gestures, and adaptive meaning-negotiation strategies. The study offers originality by situating decolonizing ELT within everyday tourism interaction and by foregrounding local English practices as legitimate communicative resources in an Indonesian coastal context. These findings suggest the need for a more contextual, communicative, and experience-based ELT pedagogy that aligns classroom learning with learners’ real-world social and economic language needs.